Social Communication of the Village Government in Socializing Waste Management in Bejijong Village - Fitria, Dhyva Angela Rahmadhani; Rochmaniah, Ainur (Procedia of Social Sciences and Humanities, 2024)
Social communication is a way for the village government to socialize waste management to residents, with social communication making it easier for the village government to socialize waste management because it is carried out jointly in a large forum and has feedback from residents. The research aims to explore information on how social communication conveyed by the Bejijong Village Government in socializing waste management, so that it can be applied by the community in Bejijong Village, especially in Rt 02 Rw 01 Bejijong Hamlet, Rt 02 Rw 01 Kedung Wulan Hamlet, Rt 03 Rw 01 Bejijong Hamlet. The problems contained in this study are the participation, perception and attitude of the community towards the social communication provided by the village government to the community for the socialization of waste management. This study uses a descriptive qualitative approach by focusing on research data that will be produced from words through a form of observation and interview. This study describes the field phenomenon through direct observation by visiting the location of socialization carried out by the village government, then conducting direct interviews with residents and village officials, and the results can be analyzed to obtain research results. The results of this study show that the social communication of the village government to the residents of Bejijong Village is very good and can be well received by the residents, with indicators in it such as understanding, fun, influence on attitudes, better relationships, and true principles of brotherhood.